ABL gene kinase domain mutation scanning by denaturing high performance liquid chromatography sequencing method - Yücel Erbilgin; Suzin Çatal; Ahmet Emre Eşkazan; Özden Hatırnaz; Teoman Soysal; Uğur Özbek (Turkish Journal of Hematology, 2011)
OBJECTIVE: Despite the efficacy of the BCR-ABL tyrosine kinase inhibitor imatinib, the development of resistance against imatinib has been observed. The most important mechanisms known to cause resistance are point mutations in the ABL tyrosine kinase and the ATP domain. This study describes the use of denaturing high performance liquid chromatography (dHPLC) as a method to screen for mutations of the ABL gene. METHODS: We used the dHPLC based assay for the screening of ABL point mutations. Forty chronic myeloid leukemia (CML) patients who showed resistance to imatinib were screened in parallel by dHPLC and direct sequencing. RESULTS: Nine of the 40 patients (23%) had mutations. CONCLUSION: dHPLC can be a useful method for pre-screening. Analyzing the mutations and monitoring (high-risk) patients can improve their prognosis and survival rate. dHPLC can potentially become a valuable tool for regular testing of patients in the future.